Credibility and Incredulity in Milgram's Obedience Experiments: A Reanalysis of an Unpublished Test. (March 2020) - Perry, Gina; Brannigan, Augustine; Wanner, Richard A.; Stam, Henderikus
This article analyzes variations in subject perceptions of pain in Milgram's obedience experiments and their behavioral consequences. Based on an unpublished study by Milgram's assistant, Taketo Murata, we report the relationship between the subjects' belief that the learner was actually receiving painful electric shocks and their choice of shock level. This archival material indicates that in 18 of 23 variations of the experiment, the mean levels of shock for those who fully believed that they were inflicting pain were lower than for subjects who did not fully believe they were inflicting pain. These data suggest that the perception of pain inflated subject defiance and that subject skepticism inflated their obedience. This analysis revises our perception of the classical interpretation of the experiment and its putative relevance to the explanation of state atrocities, such as the Holocaust. It also raises the issue of dramaturgical credibility in experiments based on deception. The findings are discussed in the context of methodological questions about the reliability of Milgram's questionnaire data and their broader theoretical relevance.